Malnutrition and Risk of Mortality in Ischemic Stroke Patients Treated With Intravenous Thrombolysis - Tang, Haiyan; Gong, Fan; Guo, Hongquan; Dai, Zheng; Wang, Jun; Liu, Bin; Li, Tingting; Tang, Xianbiao; Dong, Junru; Pan, Song; Wang, Mingzhe; Sun, Yan; et al. (Frontiers in Aging Neuroscience, 2022)
Background and Purpose: Malnutrition is highly prevalent in ischemic stroke patients. We aimed to investigate whether malnutrition indexes may be useful in predicting mortality at 90 days in ischemic stroke patients treated with intravenous thrombolysis. Methods: We retrospectively analyzed consecutive patients who underwent thrombolytic therapy at 3 comprehensive stroke centers. Malnutrition was assessed using the controlling nutritional status (CONUT) score, geriatric nutritional risk index (GNRI), and prognostic nutritional index (PNI). Results: Of 979 patients (mean age, 66.8 years; males, 63.6%) included in this study, 91 (9.3%; 95 % confidence interval [CI]: 8.4–10.2 %) died at 3-month follow up. According to the CONUT, GNRI, and PNI scores, 9.9%, 33.7%, and 7.0% of patients were moderately or severely malnourished, respectively; 64.0% were at least mildly malnourished by at least 1 malnutrition index. In the multivariate regression model after adjusting for potential confounders, malnutrition (severe risk versus normal nutritional status) was significantly associated with an increased risk of mortality for CONUT scores (adjusted odds ratio [OR] 16.16, 95%CI, 7.86-67.11; P < 0.001), GNRI scores (adjusted OR 9.82, 4.10-23.51; P < 0.001) and PNI scores (adjusted OR 12.74, 5.56-29.19; P < 0.001). Similar results were found when the malnutrition scores were analyzed as continuous variables. Adding the 3 malnutrition indexes to models containing conventional risk factors significantly improved risk reclassification for 3-month mortality. Conclusions: Our study showed that malnutrition was significantly associated with a higher risk of mortality at 3 months in ischemic stroke after intravenous thrombolysis.